The Application Of Hygiene And Sanitation To Processed Products In Restaurant Kitchen Around Tourism Destination Area In Toba District - Mohammad Yusuf Dalimunthe (Tourism, Hospitality And Culture Insights Journal, 2022)
Hygiene and sanitation in food storage is an effort to control risk factors for food contamination in the food storage process. Processing of food ingredients according to standards will slow down food spoilage so that food quality is maintained. The purpose of this study was to observe the application of internal sanitation hygiene to processed products in restaurant kitchens in Balige City, Toba Regency. As for this type of research with qualitative descriptive methods, the data collection methods used are observation methods, interview methods and documentation methods. From the results of research and field observations where the three restaurants sampled in this study have implemented hygiene and sanitation standards, especially in processing products that are in accordance with standard provisions such as washing, peeling and slicing